2018
DOI: 10.1055/s-0043-113820
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of Fetal MRI in the Evaluation of Fetal Anomalies of the Corpus Callosum: A Retrospective Analysis of 78 Cases

Abstract: Fetal MRI effectively detects callosal anomalies and enables satisfactory validation of the presence or absence of callosal anomalies identified by ultrasound and adds valuable data that improves clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…8,9 If callosal malformation is suspected an in-utero MRI is recommended. [10][11][12] Malformations of the CC can be characterized by agenesis (ACC), hypoplasia and hyperplasia. 13 The etiology for callosal malformations is usually idiopathic; however, a combination of genetic mechanisms and environmental factors is also described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 If callosal malformation is suspected an in-utero MRI is recommended. [10][11][12] Malformations of the CC can be characterized by agenesis (ACC), hypoplasia and hyperplasia. 13 The etiology for callosal malformations is usually idiopathic; however, a combination of genetic mechanisms and environmental factors is also described.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the fetal CC can be performed by trans‐vaginal or trans‐abdominal sonography . If callosal malformation is suspected an in‐utero MRI is recommended . Malformations of the CC can be characterized by agenesis (ACC), hypoplasia and hyperplasia .…”
Section: Introductionmentioning
confidence: 99%
“…Not all fetuses had both ultrasound and MRI; however, review of the studies suggested that, when expert neurosonography was performed, fetal MRI rarely changed the nature of the diagnosed CC abnormality, with MRI generally performed to better delineate small remnants of CC tissue and render a diagnosis of partial rather than complete agenesis. In studies in which fetal MRI was performed after conventional screening ultrasound exams, without added expert neurosonography, the reported discrepancy rate between MRI and ultrasound was higher 23,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Agenesis of corpus callosum (ACC) is a rare congenital central nervous system malformation, with the incidence rate of about 0.3-0.7%, and often associated with other fetal malformations [1,2]. ACC can be divided into complete and partial type in morphology, and also Isolated and Compound type with or without other malformations [3,4], different types of ACC have huge difference in prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…ACC can be divided into complete and partial type in morphology, and also Isolated and Compound type with or without other malformations [3,4], different types of ACC have huge difference in prognosis. The precise function of the corpus callosum is not clear yet, which is currently believed to mainly connect the integrated bilateral motor language centers, motor ataxia area and audio/visual area and other areas [4], and often related to pathogenesis of autism, epilepsy, schizophrenia, dementia and other diseases [2]. High-resolution color Doppler ultrasound is the most important means of prenatal screening for ACC, while the rapid development of fetal magnetic resonance imaging (MRI) has provided a new approach for fetal intracranial studies, with high image resolution and free from the influence of factors such as the position of fetus.…”
Section: Introductionmentioning
confidence: 99%